1996
DOI: 10.1097/00006534-199612000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Pedicle Thrombosis and Flap Loss after Free-Tissue Transfer

Abstract: A series of 990 consecutive free flaps was reviewed to determine how often pedicle thrombosis occurred, when it occurred, and if the timing of thrombosis detection had any relationship to the probability of flap salvage. The overall thrombosis rate was 5.1 percent, and the flap loss rate was 3.2 percent. The majority (80 percent) of thrombi occurred within the first 2 postoperative days. Only 5 thrombi (10 percent) were known to have occurred after the third postoperative day. No flaps that developed thrombosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
338
3
16

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 402 publications
(383 citation statements)
references
References 4 publications
26
338
3
16
Order By: Relevance
“…This delay is two hours for arterial thrombosis and about 4 hours for venous thrombosis. Other studies are in agreement with our results [5,6]. The value of intracapillary glucose and lactate and their respective kinetics allow early suspicion of arterial thrombosis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This delay is two hours for arterial thrombosis and about 4 hours for venous thrombosis. Other studies are in agreement with our results [5,6]. The value of intracapillary glucose and lactate and their respective kinetics allow early suspicion of arterial thrombosis.…”
Section: Discussionsupporting
confidence: 92%
“…These complications often occur in the first twenty-four hours [1,5,[12][13][14]. This acute period does not allow the creation of a microvascular network, unlike what happens in chronic occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Venous thrombosis is more than twice as common as arterial thrombosis among causes of flap failures due to pedicle thrombosis. (6) Compression due to hematoma was the cause for vascular compromise and impending flap failure in our subject. Hidalgo et al (4) identified venous problems (35%) as the most common etiology of flap failure followed by arterial problems (28%), hematoma (26%) and recipient vessel problems (11%).…”
Section: Discussionmentioning
confidence: 76%
“…Certain surgeons have hypothesized that performing two venous anastomoses (AV and SV) is imperative for the survival of flow-through flap grafts because multiple draining veins result in improved blood flow through the flap (31,32). Hanasono et al (33) considered that the blood velocity of a flap graft with two venous anastomoses did not increase significantly and resulted in a better prognosis when compared with one venous anastomosis (AV) in patients who underwent a flap graft with one or two anastomoses, due to the hypothesis that thrombosis is associated with a low-velocity state and performing two anastomoses theoretically increased the risk of thrombosis.…”
Section: A D C B E Discussionmentioning
confidence: 99%